International Rules on Maritime Delimitation - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
This paper deals with international rules which are applicable in the cases of maritime delimitation. The importance of sea and its resources incited the states to regulate their boundaries in international agreements. In the situations when it is impossible to reach an agreement on delimitation it is necessary to resolve the dispute. Among other issues, there can be differences regarding the delimitation of territorial sea, continental shelf and exclusive economic zone. The UN Convention on the Law of the Sea, which comprehensively regulates this field contains also certain rules on maritime delimitation. Besides diplomatic means, states concerned can try to resolve the dispute by using the arbitration or judicial means of dispute settlement. The jurisdiction for the dispute settlement have the International Court of Justice and the Tribunal for the Law of the Sea. They usually apply the principle of equidistance but it can be complemented or replaced with additional criteria if there are some special circumstances related to the concrete case. The basic aim in the process of decision making is the achievement of equitable and acceptable solution.